Re-Design Interior Boutique Hotel di Malang - Inez Natalia Suteja; mariana wibowo (Intra, 2016)
Malang is one of the places nostalgia tourists by Dutchman. Design boutique hotel take building's dutch colonial. Boutique hotel having the characteristics of unique, historic, and fancy. Uniqueness boutique hotel ditonjolkan in the atmosphere hotel that looks homey with support 3star class hotel facilities. The concept of the basis of design with apply a style of design colonial into the interior of boutique hotel good with the material the wall, the floor, ceiling, column and the elements decorative space. A method of design adopt new material who adapts the shape and character a style of design dutch colonial of a building the architecture was namely the dutch colonial style.